Analysis of mitochondrial D-loop region casts new light on domestic water buffalo (Bubalus bubalis) phylogeny - Kierstein, G.; Vallinoto, M.; Silva, A.; Schneider, M.P.; Iannuzzi, L.; Brenig, B. (Elsevier, 2004)
The phylogeny of water buffaloes (Bubalus bubalis) is still a matter of discussion, especially if the two types of domestic water buffalo (swamp and river) derived from different domestication events or if they are products of human selection. To obtain more insight, we analyzed the entire mitochondrial D-loop region of 80 water buffaloes of four different breeds, i.e., 19 swamp buffaloes (Carabao) and 61 river buffaloes (Murrah, Jafarabadi, and Mediterranean), sampled in Brazil and Italy. We detected 36 mitochondrial haplotypes with 128 polymorphic sites. Pooled with published data of South-East Asian and Australian water buffaloes and based on comprehensive median-joining network and population demography analyses we show evidence that both river and swamp buffaloes decent from one domestication event, probably in the Indian subcontinent. However, the today swamp buffaloes have an unravelled mitochondrial history, which can be explained by introgression of wild water buffalo mtDNA into domestic stocks. We are also discussing indications for an independent domestication of buffaloes in China.